TBIO-23. INTRACRANIAL EXTRA-SKELETAL MESENCHYMAL CHONDROSARCOMA: CASE REPORT AND META-ANALYSIS OF REPORTED CASES IN ADULTS AND CHILDREN. Issue 2 (22nd June 2018) - Shabani, Saman; Nguyen, Ha Son; Knipstein, Jeffrey; Lew, Sean; Kaufman, Bruce; Lawlor, Michael; Foy, Andrew
Abstract: INTRODUCTION: Intracranial extra-skeletal mesenchymal chondrosarcoma (IEMC) is a rare tumor that accounts for only 0.16% of primary intracranial tumors. We review our experience and the medical literature for patients with IEMC. METHOD: Case report and meta-analysis of reported IEMC. Kaplan-Meier survival test was used for statistical analysis. RESULT: Total of 71 reported cases including ours. Follow-up ranged from 3 days to 216 months. Age at diagnosis ranged from 2 month to 71 years, however the majority were under 18. There was strong female predominance. 55% had GTR versus 22% with STR. 36 (51%) patients received radiation therapy, 9 (12.7%) had chemotherapy, and 9 (12.7%) had both XRT and chemotherapy. 52/71 (73.2%) of tumors had dural attachment and the rest were purely intraparenchymal. Median overall survival was 25 months (+/- 5.392). Improved survival was noted for the first 50 months in XRT group (P= 0.032). Survival was worse with recurrence (p= 0.002). Dural based tumors had better survival compared to purely intraparenchymal tumors, but not statistically significant (p=0.071). GTR seemed to improve survival compared to STR, but was not statistically significant (p=0.455). CONCLUSION: IEMC is a malignant tumor with 45% mortality and median overall survival of 25 months. Radiation significantly increases the survival in these patients especially in the first 50-month after diagnosis. Recurrence significantly decreases survival. Although GTR seems to increase survival, this was not statistically significant. The effect of chemotherapy on survival cannot be determined.